The diagnosis and management of pleural empyema. - Davies, R; Gleeson, F (1998)
The diagnosis and management of pleural infection continues to improve steadily. Recent advances include: newer, smaller, and more comfortable chest drainage catheters; improved pleural pus drainage with the aid of intrapleural fibrinolytics; and improved surgical procedures including thoracoscopic surgery. The optimal size of chest drainage tube remains a matter of debate, with no large data sets available to clarify the optimal tube size. In contrast, there are now small controlled trials of sound basic methodology which suggest a therapeutic role for both fibrinolytics and thoracoscopy. Studies large enough to establish clearly the efficacy and safety of these approaches are now at the planning and recruitment stage.